Flexible learning as a new designed pedagogy: The nursing students' lived experiences - Kristine A. Condes; Anamae G. Quezon (Northern Negros State College of Science and Technology (NONESCOST), 2021)
The compelled shift of pedagogy design in nursing education as a result of the COVID-19 pandemic has brought some disparities and challenges in the program, more specifically to the students. The purpose of this study is to explore the lived experiences of nursing students with flexible learning. Using a qualitative phenomenological research design, a one-on-one interview via zoom has been utilized to understand the perception and views of six nursing students who qualified in the inclusion criteria set by the researchers. Specifically, it gives light on their views of flexible learning, the challenges they encountered, and their adaptation methods. The findings show that participants experienced difficulties and made huge adjustments in their routines and approaches to learning. The absence of clinical exposure and the gap in skills and related learning experience in nursing education is their most concerning aspect. However, even with all the gaps and limitations of flexible learning, it also offers unique advantages to them. Participants cited flexibility, self-paced learning, self-discipline, time management, convenience, and time for the family were their positive experiences. The result draws four thematic insights from the experiences of the participants: Sudden Shift of Learning Design is a Tough Change, Gap in the Practical Component of Nursing Education, Flexible Learning is Taking Shape, and Staying Positive with Creative Outlets. The study recommends that nursing institutions and organizations should look into the limitation of resources among nursing students and come up with programs and strategies that would address the gap of skills and practical components in nursing education. Acknowledgment of these limitations should make the nursing schools and administrators come up with some alternatives in the delivery of education as the students adjust to the new learning design.